3(x-4)² - 72 = 0
3(x-4)² = 72
(x-4)² = 24
x - 4 = ±√24 = ±2√6
x = 4 ± 2√6
2007-02-01 13:12:23
·
answer #1
·
answered by Philo 7
·
0⤊
0⤋
Square the x-4, (x^2+16), then multiply it by 3, (3x^2+48-72), combine like terms, (3x^2-24=0) now, add 24 to both sides, (3x^2=24), divide by 3 (x^2=8) and you have the square root of 8=x
2007-02-01 21:14:48
·
answer #2
·
answered by nightdrake66 2
·
0⤊
0⤋
you could also use the quadratic formula...
[-b +/- root(b^2-4ac)]/2a
what do you plug in?
expand the question... and get
3x^2 - 24x +48 -72=0
3x^2 - 24x - 24= 0
(a=3, b= -24, c= -24)
the answer turns out to be the same thing
2007-02-01 21:24:13
·
answer #3
·
answered by suggargurl302 2
·
0⤊
0⤋
3(x-4)² - 72 = 0
3(x² - 8x + 16) - 72 = 0
3x² - 24x + 48 -72 = 0
3x² - 24x - 24 = 0
x² - 8x - 8 =0
for
ax² + bx + c = 0
x = (-b ±â(b² - 4ac)) / 2a
x = (8 屉(64 - 4*1*-8)) / 2
x = (8 屉96) / 2
x = ( 8 ± 4â6) /2
x = 4 ± 2â6
x = 8.9 or x = -0.9
2007-02-01 21:13:30
·
answer #4
·
answered by M. Abuhelwa 5
·
0⤊
0⤋